Fiber optic sensor for the measurement of surface roughness due to corrosion - Sukiman Hakimi Che Ahmad, 1986-; Asiah Yahya, supervisor; Fakulti Sains (2012)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2012